Correlation between Red Cell Distribution Width and Coronary Artery Disease Severity in Non-Diabetic Patients of Punjab Institute of Cardiology (PIC) (Journal of Fatima Jinnah Medical University, 2024)
Background: Coronary artery disease (CAD) is one of the major causes of morbidity and mortality. Recently, red cell distribution (RDW) width has emerged as a marker of CAD severity. This study aimed to evaluate the correlation between RDW and CAD severity. Compared with angiography, which is cost-effective but time-consuming, this simple test can be performed before angiography to assess CAD severity. This will reduce patient burden in tertiary care hospitals and also decrease the patient anxiety rate regarding an invasive process like angiography. Patients and methods: This cross-sectional analytical study was conducted at the Punjab Institute of Cardiology (PIC), Lahore. Eighty patients who underwent coronary angiography were selected. The Gensini score was used to calculate CAD severity. RDW was obtained from an automated haematology analyzer. The correlation between RDW and Gensini score was then statistically analysed by Spearman's correlation. A total of eighty patients undergoing “elective “coronary angiography were selected (inclusion criteria). Patients with diabetes mellitus, cerebral infarction, haematological diseases, hepatic diseases, and renal diseases were excluded (exclusion criteria). There were 57 males and 23 females. It was graded and classified only. The severity score (for vessel wall blockage) ranges from 1 to 32 and was included. Results: The study population included 57 (71.3%) males and 23 (28.7%) females. The mean age of the population was 55.28±11.1 years. Among the 80 patients, 71 (71/80, 88.75%) were diagnosed with CAD on angiography and out of these, 21 (21/71, 29.5%) patients had one vessel disease, 22 (22/71, 28.5%) had two vessel disease, and 28 (28/71, 39.4%) had three vessel disease. The median and IQR of the Gensini score of the whole population were 28 (6.5-56). With one vessel involvement, the median and IQR were 10 (5.7-30); with two vessel involvement, 34 (14-56); and with three vessel involvement, 56 (29-99). A non-significant correlation was observed between RDW and the Gensini score (rho = 0.028, p = 0.808). Rho (is the strength of association between two variables.)Conclusion: No significant correlation between RDW and coronary artery disease severity was observed; sample size may have been a limiting factor.
Keywords: Red cell distribution width; coronary artery disease; Gensini score